2020
DOI: 10.1093/gerona/glaa236
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Health Care Use by Mexican American Medicare Beneficiaries Before and After a Diagnosis of Dementia

Abstract: Background Evidence from predominantly non-Hispanic White cohorts indicates healthcare utilization increases before Alzheimer’s disease and related dementias (ADRD) is diagnosed. We investigated trends in healthcare utilization by Mexican-American Medicare beneficiaries before and after an incident diagnosis of ADRD. Methods Data came from the Hispanic Established Populations for the Epidemiologic Study of the Elderly that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Furthermore, Hispanics may more readily accept provider advice compared to other races/ethnicities [ 43 ]. For instance, Hispanics have decreased hospitalization and emergency department visitations after diagnosis of AD-related dementia compared to prior to diagnosis [ 43 ]. This may indicate that Hispanics are more proactive in using their newfound health knowledge to prevent further complications.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hispanics may more readily accept provider advice compared to other races/ethnicities [ 43 ]. For instance, Hispanics have decreased hospitalization and emergency department visitations after diagnosis of AD-related dementia compared to prior to diagnosis [ 43 ]. This may indicate that Hispanics are more proactive in using their newfound health knowledge to prevent further complications.…”
Section: Discussionmentioning
confidence: 99%
“…We found some researches studying only a portion of healthcare use using MCA but conducted in populations different from ours. [31][32][33][34][35] Overall, studies describing healthcare use before and after ADRD identification showed an increased healthcare use before ADRD identification followed by an increased, 16,18 decreased 13,14 or stable 17 healthcare use after ADRD identification. If studies investigated healthcare trajectories before, after, or before and after an incident ADRD diagnosis, to our knowledge, none studied the association between healthcare use before ADRD diagnosis and future favorable healthcare trajectories after ADRD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no study confronted, with such wide approach, the healthcare use before ADRD identification and a long‐term healthcare trajectory after ADRD. Some studies described healthcare use before and after ADRD identification, however none confronted healthcare use in these two periods 13,14,16–18 . Therefore, the extent to which some patterns of healthcare use preceding ADRD may be more prone to further favorable healthcare trajectories is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations